Pemakaian Eufemisme Pada Tajuk Rencana Solopos Edisifebruari-Maret 2017 Dan Implikasinya Sebagai Bahan Ajar Bahasa Indonesia Di Smp Kurikukulum 2013 Kd 4.1 - Nawangwulan, Ajeng, Drs. Andi Haris Prabawa, M.Hum (2017)
This study aims to describe the form and meaning of phemism that is implied as Indonesian language teaching materials in Junior High School 8 th grade/ 8 th grade of Junior High School. This research uses descriptive qualitative research method. Data collection is done by library method, see and note. Data analysis used is method of agih with technique of replace and referential padan with semantic approach. Agih method with replace technique is used to find the form of language of euphemism, while referential padan method with semantic approach to describe the meaning of euphemism. The validity of data using triangulation theory and peers.The result of this study include the forms of euphemism found in this study includes: figurative expressions, one word substituting another words, abbreviations, usage of the word absorption, flipansi, use of foreign languages, metaphors, idioms, hyperbole, circulation and acronyms. These forms have high values meanings used to avoiding catastrophe, disguising meaning, as a form of polite expression, keeping something secret, as a means of diplomacy, avoiding taboos, a means to soften speech, to reduce shame and to carry out religious commands. The use of this euphemism language can be applied as teaching material for 8 th grader of Junior High School. It uses 2013 curricullum. The main focus is review text. The text of this review is the same as an editorial review of an existing phenomenon. Keywords: euphemism, meaning, teaching materials